Error Analysis for Localization of Multisensory Cues for Countering Spatial Disorientation. (September 2018) - Brill, J. Christopher; Gibson, Anthony; Lawson, Ben D.; Rupert, Angus H.
Decrements in situation awareness (SA) remain an important research topic, due to its influence on spatial disorientation (SD). Multisensory displays (e.g., three-dimensional audio and audiotactile displays) present potential solutions to SD related to SA loss. The current study investigated the differences in performance across six different modality conditions (i.e., visual, audio, tactile, audiotactile, visuotactile, and audiovisual). The results indicated that localization errors were largest when participants were provided with auditory cues, which is consistent with prior research findings.